2018
DOI: 10.1177/1744629518798259
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of psychiatric disorders in people with intellectual disabilities: Differences between psychiatric disorders and challenging behaviour

Abstract: The presence of a psychiatric as well as a medical comorbidity is associated with severe ID, unlike challenging behaviour. Clinical limitations of the study have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Considering the severity of intellectual disability, the present authors found seven studies accounting for 445 subjects showing data for mild intellectual disability (Crews et al, ; Deb et al, ; Göstason, ; Iverson & Fox, ; Lund, ; Peña‐Salazar et al, ; Salvador‐Carulla et al, ), seven studies accounting for 408 showing data for moderate intellectual disability (Crews et al, ; Deb et al, ; Holden & Gitlesen, ; Iverson & Fox, ; Lund, ; Peña‐Salazar et al, ; Salvador‐Carulla et al, ), six studies accounting for 364 showing data for severe intellectual disability (Crews et al, ; Göstason, ; Holden & Gitlesen, ; Lund, ; Peña‐Salazar et al, ; Salvador‐Carulla et al, ) and four studies accounting for 986 showing data for profound intellectual disability (Crews et al, ; Holden & Gitlesen, ; Lund, ; Peña‐Salazar et al, ). The pooled prevalence of co‐occurring psychiatric disorder was similar in mild intellectual disability (29.1%, 95% CI: 19.3%–41.4%), moderate intellectual disability (28.5%, 95% CI: 19.5%–39.6%) and severe intellectual disability (33.5%, 95% CI: 16.5%–56.2%), and lower in profound intellectual disability (22.4%, 95% CI: 7.8%–49.7%).…”
Section: Resultsmentioning
confidence: 67%
“…Considering the severity of intellectual disability, the present authors found seven studies accounting for 445 subjects showing data for mild intellectual disability (Crews et al, ; Deb et al, ; Göstason, ; Iverson & Fox, ; Lund, ; Peña‐Salazar et al, ; Salvador‐Carulla et al, ), seven studies accounting for 408 showing data for moderate intellectual disability (Crews et al, ; Deb et al, ; Holden & Gitlesen, ; Iverson & Fox, ; Lund, ; Peña‐Salazar et al, ; Salvador‐Carulla et al, ), six studies accounting for 364 showing data for severe intellectual disability (Crews et al, ; Göstason, ; Holden & Gitlesen, ; Lund, ; Peña‐Salazar et al, ; Salvador‐Carulla et al, ) and four studies accounting for 986 showing data for profound intellectual disability (Crews et al, ; Holden & Gitlesen, ; Lund, ; Peña‐Salazar et al, ). The pooled prevalence of co‐occurring psychiatric disorder was similar in mild intellectual disability (29.1%, 95% CI: 19.3%–41.4%), moderate intellectual disability (28.5%, 95% CI: 19.5%–39.6%) and severe intellectual disability (33.5%, 95% CI: 16.5%–56.2%), and lower in profound intellectual disability (22.4%, 95% CI: 7.8%–49.7%).…”
Section: Resultsmentioning
confidence: 67%
“…Mental illness in people with intellectual disability can be difficult to accurately diagnose due to atypical behavioral manifestations of disorders and hence a high level of diagnostic uncertainty can exist. A recent population-based study of 142 people with intellectual disability showed that almost one-third of participants in congregate settings had an undiagnosed mental disorder, with major depressive and anxiety disorders most common [23]. CMD were found to be an important predictor of adverse outcome in this study, suggesting a need for optimization of ascertainment and treatment of underlying mental ill-health to improve outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…One study focused on both disorders and symptoms (Tyrer et al., 2006). To diagnose, a person with intellectual disability with a psychiatric disorder is not easy, especially with increasing levels of disability (Flynn et al., 2017; Peña‐Salazar et al., 2018). Difficulties may originate from communication difficulties, cognitive issues or atypical presentations of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, there is not sufficient evidence to determine which factors are most likely to contribute to the emergence or continuation of aggressive behaviour, although the current review suggests that certain behavioural, psychiatric and psychosocial factors may contribute. In light of the much mentioned diagnostic overshadowing (Peña‐Salazar et al., 2018), it is recommended that such factors are part of the functional assessment. To better guide functional assessments, it is imperative that more research on factors contributing to aggressive behaviour is undertaken, which also focuses on understanding the causality of the associations.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%